Mobile Food Record 24 Hour Recall (mFR24) Was "Easy" and an Acceptable Mobile Health Dietary Assessment Method. (14th June 2022) - Healy, Janelle; Boushey, Carol; Delp, Edward; Zhu, Fengqing; Collins, Clare; Rollo, Megan; Wright, Janine; Hassan, Amira; Whitton, Clare; Pollard, Christina; Dahliwal, Satvinder; Kerr, Deborah
Abstract: Objectives: Technology has increased the availability of mobile health (mHealth) apps for dietary assessment. The 24 hour recall (24 HR) is the current preferred method to monitor population diet related health and nutritional status to inform public health nutrition policies. A novel labelled image assisted 24 HR has potential to enhance engagement with consumers but needs to be evaluated for acceptability and accuracy. 1. To identify features of an image-assisted mobile 24 HR (mFR24) that are enablers or barriers to its acceptable use in adult dietary assessment. Methods: Controlled feeding study participants recorded before and after images of food and beverages consumed at three meals in a single day using the mobile app. The next day, they labelled the items in their images from a food list in the app linked to a food composition database; before an interview assisted 24 HR and using the novel labelled images. Participant's acceptability perceptions of the mFR24 were asked via an online survey using a 5-point Likert scale to rate their agreement with statements including how easy it was to find and remember foods and amounts consumed, and if they would be willing to use the mFR24 again. Results: Participants (n = 134) were mainly female (57%), under 35 years (63%), held a bachelor degree or higher (75%), identified as Asian (67%), in full time employment (46%) or a student (34%). Two thirds (68%) of participants reported usually taking photos of their food, 90% agreed it was 'easy' to record their intake using the app. When undertaking the 24 HR, participants agreed using labelled images of their food and beverages made it easy to remember foods (95.4%) and amounts eaten (93.2%). The majority (88.6%) were willing to undertake the mFR24 method again. Age, gender, previous weight loss history and usually taking food photos were not found to be associated with the ease of mFR24 use. Conclusions: Labelled image based mFR24 method of dietary intake assessment hold promise for being an easy and acceptable population dietary assessment method to inform dietary guideline advice. Investigating the accuracy of the labelled image mFR24 will be the next step in the investigation of the novel mFR24. Funding Sources: This study was funded by an Australian Research Council Discovery Project 190, 101, 723. The mobile food record is funded by NIH, NCI (1U01CA130784-01); NIH, NIDDK (1R01-DK073711-01A1).